Нефть Столбового месторождения - Сечина Т. В. Тамара Владимировна; Смольянинов С. И. Станислав Иванович; Немировская Г. Б. Галина Борисовна; Кушникова С. Г. Светлана Гурьевна; Галашова Н. И. Наталья Ивановна; Зюлковская Э. А. Эльвира Александровна (Томск, 1989)
Деп. в ЦНИИТЭНефтехим 10.10.89, № 192-НХ-89.